The Megameatus, Intact Prepuce Variant of Hypospadias: Use of the Inframeatal Vascularized Flap for Surgical Correction - Cendron, Marc (Frontiers in Pediatrics, 2018)
Introduction The megameatus intact prepuce variant of hypospadias (MIP) is a rare variant of hypospadias that is diagnosed either early at the time of circumcision or later as the foreskin is retracted. The true incidence of the anomaly is difficult to determine precisely as some patient never come to medical attention but is felt to under 5% of all cases of hypospadias. The purposes of this study are to review the embryology and clinical findings of MIP and then, in light of a personal experience, present a series of patients evaluated for MIP who were treated with a modification of the Mathieu technique. Materials and Methods A PubMed search of all articles in the MIP variant of hypospadias was carried out followed by an exhaustive review of the literature. The charts of all patients evaluated and treated at Boston Children’s Hospital by MC between 2007 and 2017 were reviewed retrospectively. The patients were divided into two groups: those who underwent the standard procedure and those who underwent a repair using a modification of the Mathieu procedure using an infra-meatal flap. Results The embryologic explanation of the MIP variant is not clear but failure of the distal, glanular portion of the urethra to tubularize results in spectrum of abnormality characterized by a deep glanular groove and an abnormal opening of the urethra anywhere from the mid-glans to a sub-coronal location. Surgical repair is complicated by a wide distal urethra which may be injured if not properly identified. Overall satisfactory outcomes were noted with one patient experiencing a urethra cutaneous fistula in the first group and one patient having a mild glans dehiscence in the second. Conclusions The MIP variant of hypospadias is a rare variant of hypospadias that presents as a spectrum of urethral anomaly. Surgical repair may not always be necessary but if surgical repair is carried out, the Mathieu technique modification may offer better anatomic delineation of the urethra and will provide an extra layer of tissue to cover the reconstructed urethra. Low complication rates should be expected with adequate functional outcome such as a normal urinary stream. In